Potensi Pencahayaan Alami pada Bangunan Peribadatan Gereja GPIB Filadelfia Semarang - Varinca Augi Tahapary; Chely Novia Bramiana (Universitas Diponegoro, 2024)
Natural lighting is one of the supporting functions of space that can positively impact space users. One of the benefits is visual comfort when carrying out various indoor activities. Visual comfort is needed in every room, including the worship room. This study aims to evaluate the intensity of natural lighting in the GPIB Filadelfia Church Semarang church hall. This research uses the quantitative method by doing direct observations and measurements using a lux meter placed at twelve measuring points during sunny weather. The results showed that the average light intensity in the morning, afternoon, and evening complies with the visual comfort standards of SNI 03-6197-2000; thus, overall visual comfort is achieved. However, some measuring points with small lighting intensity are still not up to standards because the location is too far from the openings. A light barrier also affects the difference in light intensity at each measuring point.